Proceedings of the 31st Annual ACM/IEEE Symposium on Logic in Computer Science 2016
DOI: 10.1145/2933575.2933595
|View full text |Cite
|
Sign up to set email alerts
|

Upper Bounds on the Quantifier Depth for Graph Differentiation in First Order Logic

Abstract: We show that on graphs with n vertices the 2-dimensional Weisfeiler-Leman algorithm requires at most O n 2 / log(n) iterations to reach stabilization. This in particular shows that the previously best, trivial upper bound of O(n 2 ) is asymptotically not tight. In the logic setting this translates to the statement that if two graphs of size n can be distinguished by a formula in first-order logic with counting with 3 variables (i. e., in C 3 ), then they can also be distinguished by a C 3 -formula that has qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We should remark that while the combinatorial techniques from [12] showing the upper bound of O(n 2 / log n) also translate to the setting without counting, our techniques seem to strongly rely on counting, since only the counting itself ensures the correspondence to matrix algebras that we exploit.…”
Section: Our Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…We should remark that while the combinatorial techniques from [12] showing the upper bound of O(n 2 / log n) also translate to the setting without counting, our techniques seem to strongly rely on counting, since only the counting itself ensures the correspondence to matrix algebras that we exploit.…”
Section: Our Techniquementioning
confidence: 99%
“…With regard to lower bounds, Fürer [8] proved that there are graphs on which the stabilization number is in Ω(n). In [12], using combinatorial techniques and a case distinction into small and large vertex-color classes, the currently best upper bound of O(n 2 / log n) for the iteration number was proven. In this paper we take an algebraic approach to the problem and show the following upper bound.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly as for Colour Refinement, one can consider the number WL k (n) of iterations of k-WL on graphs of order n. Notably, contrasting our results for Colour Refinement, in [21], it was first proved that the trivial upper bound of WL 2 (n) ≤ n 2 − 1 is not even asymptotically tight (see also the journal version [22]). This foundation fostered further work, leading to an astonishingly good new upper bound of O(n log n) for the iteration number of 2-WL [27].…”
Section: Related Workmentioning
confidence: 73%
“…Figure 1, which is an important feature in social network analysis. Therefore, it has been generalized to k-tuples leading to a more powerful graph isomorphism heuristic, which has been investigated in depth by the theoretical computer science community [Cai et al, 1992;Kiefer and Schweitzer, 2016;Babai, 2016;Grohe, 2017]. In Shervashidze et al [2011], the 1-WL was first used to obtain a graph kernel, the so-called Weisfeiler-Lehman subtree kernel.…”
Section: Introductionmentioning
confidence: 99%
“…Kiefer et al, 2015]. Moreover, upper bounds on the running time[Berkholz et al, 2013], and the number of iterations for k = 1[Kiefer and McKay, 2020], and the number of iterations for k = 2[Kiefer and Schweitzer, 2016;Lichter et al, 2019] have been shown. For k = 1 and 2, Arvind et al[2019] studied the abilities of the (folklore) k-WL to detect and count fixed subgraphs, extending the work ofFürer [2017].…”
mentioning
confidence: 99%